Isolation and Identification of Halotolerant Bacteria in Saline Soils from the Coastal Areas of Oebelo White Sand Beach and Pariti Beach - Yosep Lawa; Serlina Utami; Rut Delviana Lede Kore; Yantus A. B. Neolaka; Arvinda Ceniorita Lalang; Jacky Anggara Nenohai; Maria Anastasia Kutu Woa (Jurnal Beta Kimia, 2025)
A study has been conducted to isolate and identify halotolerant bacteria in saline soils from the coastal areas of Oebelo White Sand Beach and Pariti Beach. The sampling method used was random sampling. During sampling, pH, electrical conductivity (EC), and soil temperature were also measured. Bacterial isolation was performed using a serial dilution technique, resulting in three pure isolates from each beach sand sample. The isolates were cultured on Nutrient Agar (NA) medium and incubated at 37°C for 24 hours. The colonies obtained were small, round, and white. The isolates were then purified using the streak plate method. The halotolerant test was conducted using Tryptic Soy Agar (TSA) medium without added salt. The results showed that the bacterial colonies were halotolerant, as indicated by growth after 24 hours of incubation. Further biochemical tests, including motility, citrate utilization, urease, and sugar hydrolysis, revealed that all isolates from Oebelo White Sand samples showed positive results for all tests, whereas isolates from Pariti Beach exhibited some variations. These findings indicate that the isolates were capable of hydrolyzing urea into ammonia, utilizing citrate as a carbon and energy source, and fermenting sugars present in the medium.